EFFECT OF SPLIT APPLICATION OF POTASH ON YIELD AND YIELD RELATED TRAITS OF BASMATI RICE - Z. Manzoor; T. H. Awan; M. Ahmad; M. Akhter; F. A. Faiz (Journal of Animal and Plant Sciences, 2008)
Effect of split application of recommended dose of potash on the yield and yield components of rice was studied at Rice Research Institute Kala Shah Kaku during Kharif season of two years i.e. 2006 & 2007. In this investigation a recommended dose of potash fertilizer (62 kg ha-1) was tested in six different treatments i.e. T1 (all potash applied as basal), T2 (all potash applied at 25 DAT) T3 (all potash applied at 45 DAT), T4 (½ potash applied as basal and remaining ½ at 25 DAT), T5 ( ½ potash applied at 25 DAT and remaining ½ at 45 DAT) and T6 (1/3 potash applied as basal, 1/3 at 25 DAT and remaining 1/3 at 45 DAT). The treatment T1, where whole potash was applied as a basal was compared with five other treatments. Means of paddy yield and yield components of rice averaged across two years showed that maximum value of plant height (126.62cm), tillers per hill (20.22), panicle length (28.74 cm), No. of grains per panicle (103.80), 1000 grains weight (20.91 gm) and paddy yield (3.34 t/ha) were obtained in treatment receiving split use of Potash as ½ at 25 DAT and ½ at 45 DAT. Treatment T2 where whole potash was applied at 25 DAT ranked at second and least value of yield (2.86 t/ha) and all yield related attributes were achieved in the treatment T1 where all potash was applied as basal. The increased grain yield of rice with split applying of potash in T5 may be due to continuous supply of K to crop during crop growth stages. The efficient potash uptake by rice plant results in better growth and development when applied at maximum tillering stage (25 DAT) and at panicle initiation stage (45 DAT).
Keywords: Potash; rice; split application; Yield and yield traits